The Effects of Work from Home (WFH) and Work-Life Balance on Employee Performance - Wijaya, Agung; Riandi, Muhammad Hafiz (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – This study aims to examine the effects of the Work from Home (WFH) policy and Work-Life Balance (WLB) on employee performance in the Corporate Human Capital and Corporate University (CHCU) division of PT United Tractors Tbk. Design/Methodology/Approach – This study employs an explanatory quantitative research design. The population consists of 40 permanent employees of the CHCU division, all of whom were selected as respondents using a saturated sampling technique. Primary and secondary data were collected through Likert-scale questionnaires and interviews with senior employees holding team leader positions. The data were analyzed using SPSS version 27 to examine the direct and simultaneous effects of WFH policy and work-life balance on employee performance. Findings – The results indicate that the implementation of the WFH policy has a positive and significant effect on employee performance. Work-Life Balance also has a positive and significant effect on employee performance. Furthermore, WFH policy and Work-Life Balance simultaneously have a significant influence on employee performance, with a coefficient of determination (R²) of 84.9%. These findings demonstrate that effective remote work implementation and balanced work-life conditions are important factors in maintaining and improving employee performance. Originality/Value This research is original in simultaneously analyzing WFH and work-life balance within a specialized corporate division context. The findings provide practical value by offering evidence-based guidance for organizations to optimize remote work policies while supporting employee well-being.